Implementasi Konsep Bagi Hasil Produk Pembiayaan Ditinjau Dari Fatwa DSN-MUI Nomor 14 DAN 15 Tahun 2000 (Study Kasus Bank Syariah Mandiri KCP Curup) - Ranaswijaya, Ranaswijaya (Disclosure: Journal of Accounting and Finance, 2021)
The purpose of this study is to find out how to apply the concept of profit sharing to financing products at Bank Syari'ah Mandiri KCP Curup which includes financial administration records which will be analyzed with DSN fatwa no. 14/DSN-MUI/IX/2000 and the profit-sharing method analyzed by DSN fatwa no. 15/DSN-MUI/IX/2000. This research is a field research with a qualitative descriptive approach. The main data source of this research comes from field data by collecting data from informants. The results showed that the profit sharing at Bank Syari'ah Mandiri KCP Curup was applied to Chanelling financing and Revolving Fund Financing. In terms of recording financial administration, when the transaction is related to bank disbursements the method used is accrual basis while when the transaction is related to bank receipts the method used is cash basis. This is in accordance with DSN fatwa no. 14/DSN-MUI/IX/2000. Chanelling financing method used is revenue sharing and Revolving Fund Financing cannot be classified into profit sharing or revenue sharing, the determination of the amount of bank profit is based on the use of capital by customers each month as seen from customer account mutations so that it is not relevant to DSN fatwa no. 15/DSN-MUI/IX/2000.